BET proteins inhibitor JQ-1 impaired the extinction of remote auditory fear memory: An effect mediated by insulin like growth factor 2. (15th October 2020) - Duan, Qiong; Huang, Fu-Lian; Li, Song-Ji; Chen, Kang-Zhi; Gong, Li; Qi, Jun; Yang, Ze-Hua; Yang, Tian-lun; Li, Fang; Li, Chang-Qi
Abstract: Fear extinction is an important preclinical model for behavior therapy in human anxiety disorders, such as post-traumatic stress disorder (PTSD). Histone acetylation is involved in the extinction of fear memory. As the "readers" of histone acetylation markers, the role of the bromodomain and extraterminal domain (BET) proteins in fear extinction is still unclear. In the present study, we found that suppression of BET proteins using small molecule JQ-1 had no effects on the acquisition of auditory fear or on the extinction of recent auditory fear, but it impaired the extinction of remote auditory fear. We found that insulin like growth factor 2 (IGF-2) mRNA and protein were up-regulated in the anterior cingulate cortex (ACC) after the extinction training of remote fear memory, and that this effect was inhibited by JQ-1 administration. Further, the local delivery of IGF-2 protein to the ACC region rescued the impaired extinction of remote memory caused by JQ-1 administration, which suggesting IGF-2 mediates the effects of JQ-1 on remote memory extinction. Gene expression profiling analysis demonstrated that JQ-1 treatment inhibited the up-regulated expression of a key set of neuroplasticity-related genes following remote memory extinction. Together, these findings establish BET proteins as epigenetic mediator for the extinction of remote fear memory. In particular, the findings of this study imply that as a prospective preclinical cancer drug, JQ-1 (or other BET bromodomain inhibitors) should be modified to prevent it from crossing the blood brain barrier and causing neurological side effects. Highlights: BET proteins inhibitor JQ-1 selectively impaired the extinction of remote fear memory. Extinction training of remote fear increased the expression of IGF-2 in the ACC, which was inhibited by JQ-1. Injection of IGF-2 protein into the ACC rescued the impairment effects of JQ-1 on the extinction of remote fear. JQ-1 treatment inhibited the up-regulation of the expression of a key set of neuroplasticity-related genes.